FRI0213 Raynaud's phenomenon in primary sjÖgren's syndrome. prevalence and clinical characteristics in a series of 320 patients. (1st June 2001) - Garcia-Carrasco, M; Ramos-Casals, M; Rosas, J; Siso, A; De la Red, G; Trejo, O; Gil, V; Cervera, R; Font, J; Ingelmo, M
Abstract : Background: Objectives: To determine the prevalence of Raynaud's phenomenon (RP) in a large series of patients with primary Sjögren's syndrome (SS) and to identify the clinical and immunological features related to its presence. Methods: In a cross-sectional study, we investigated 320 consecutive patients with primary SS (294 women and 26 men; mean age at onset 60 years; range 16–87 years). All patients fulfilled 4 or more of the diagnostic criteria for SS proposed by the European Community Study Group in 1993. Diagnosis of RP was done in SS patients with intermittent attacks of digital pallor and/or cyanosis, in the absence of any other associated disease or anatomical abnormalities. Results: Raynaud's phenomenon (RP) was present in 40 (13%) patients. All were women, with a mean age of 57 years (range, 18 to 78 years). RP precedes onset of sicca symptomatology in 18 (45%) patients. The main triggering factor was cold exposure, which induced RP in all patients, emotional stress in 12 and 2 patients had labour predisposition. Fifteen (38%) patients required pharmacological treatment with calcium channel blockers (12 patients) or angiotensin-converting enzyme inhibitors (2 patients) in the cold seasons. One patient required treatment with intravenous prostacyclin for ischaemic complications. When compared with SS patients without RP, those with RP showed a higher prevalence of articular involvement (50% vs 31%, p = 0.031), cutaneous vasculitis (30% vs 11%, p = 0.003), antinuclear antibodies (95% vs 65%, p < 0.001), anti-Ro/SS-A (59% vs 31%, p < 0.001) and anti-La/SS-B antibodies (44% vs 20%, p = 0.003). Conclusion: We found RP in a 13% of patients with primary SS. Interestingly, RP was the first autoimmune symptomatology in almost 50% of these patients. These patients constituted a subset of SS with a higher frequency of some extraglandular features and positive immunological markers. In contrast, RP have a milder course in primary SS, with no vascular complications and needing pharmacological treatment in only 40% of patients. The clinical course of RP seems to be milder in patients with primary SS than in other systemic autoimmune diseases such as systemic sclerosis.